2021
DOI: 10.2967/jnumed.121.262473
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 PET/CT imaging with radiolabeled durvalumab in patients with advanced stage non-small cell lung cancer.

Abstract: significant (median SUVpeak 4.9 vs 2.4, p=0.06). SUVpeak correlated better with the combined tumor and immune cell PD-L1 score than with PD-L1 expression on tumor cells, although both were not statistically significant (p = 0.06 and p = 0.93, respectively). Conclusions 89Zr-durvalumab was safe without any tracer related adverse events and more tumor lesions were visualized using the tracer dose only imaging acquisition. 89 Zr-durvalumab tumor uptake was higher in patients with response to durvalumab treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 27 publications
4
43
1
Order By: Relevance
“…This effect was most pronounced with a low antibody dose of 30 µg and could be compensated for by increasing the antibody doses to 100 µg. This dose-dependent clearance from circulation has also been observed in clinical studies (20). Moreover, these results are in line with other studies that show that 10F.9G2 and other anti-PD-L1 antibodies exhibit target-mediated drug disposition (TMDD), meaning that these antibodies show nonlinear pharmacokinetics at low doses, while increasing the dose leads to linear pharmacokinetics (30,31).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This effect was most pronounced with a low antibody dose of 30 µg and could be compensated for by increasing the antibody doses to 100 µg. This dose-dependent clearance from circulation has also been observed in clinical studies (20). Moreover, these results are in line with other studies that show that 10F.9G2 and other anti-PD-L1 antibodies exhibit target-mediated drug disposition (TMDD), meaning that these antibodies show nonlinear pharmacokinetics at low doses, while increasing the dose leads to linear pharmacokinetics (30,31).…”
Section: Discussionsupporting
confidence: 89%
“…Various preclinical studies in onco-immunology have demonstrated the feasibility of this approach in immunocompetent mouse models ( 17 19 ). Moreover, recent clinical studies using a radiolabeled anti-PD-L1 antibody ( 14 , 20 ), adnectin ( 15 ), peptide ( 21 ), or nanobody ( 22 ) demonstrated that nuclear imaging using PD-L1 targeting tracers can assess PD-L1 expression in vivo ( 18 ). Accumulation of the radiolabeled anti-PD-L1 antibodies was also observed in tissues with physiological PD-L1 expression (e.g., spleen, lymph nodes, and bone marrow) as well as in inflammatory sites ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contradicting correlations have been found between clinical whole-body PD-L1 PET imaging and treatment response [ 22 , 23 , 60 , 61 ]. Our multimodal platform enabled us to image aPD-L1 tracer localization with cellular resolution with NIR fluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…to demonstrate tumor uptake in a range of advanced malignancies [93,94,102,103]. A study of [ 89 Zr]-atezolizumab, including 22 patients with advanced NSCLC, bladder or breast cancer, demonstrated tumor uptake with inter-and intra-tumoral heterogeneity, and better correlation with clinical response than with PD-L1 immunohistochemistry and RNA-sequenced immune biomarkers [94].…”
Section: Imaging Immune Checkpoint Pathwaysmentioning
confidence: 99%